If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -25)(3x + 25) = 0 Reorder the terms: (-25 + 5x)(3x + 25) = 0 Reorder the terms: (-25 + 5x)(25 + 3x) = 0 Multiply (-25 + 5x) * (25 + 3x) (-25(25 + 3x) + 5x * (25 + 3x)) = 0 ((25 * -25 + 3x * -25) + 5x * (25 + 3x)) = 0 ((-625 + -75x) + 5x * (25 + 3x)) = 0 (-625 + -75x + (25 * 5x + 3x * 5x)) = 0 (-625 + -75x + (125x + 15x2)) = 0 Combine like terms: -75x + 125x = 50x (-625 + 50x + 15x2) = 0 Solving -625 + 50x + 15x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '5'. 5(-125 + 10x + 3x2) = 0 Factor a trinomial. 5((-25 + -3x)(5 + -1x)) = 0 Ignore the factor 5.Subproblem 1
Set the factor '(-25 + -3x)' equal to zero and attempt to solve: Simplifying -25 + -3x = 0 Solving -25 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + -3x = 0 + 25 Combine like terms: -25 + 25 = 0 0 + -3x = 0 + 25 -3x = 0 + 25 Combine like terms: 0 + 25 = 25 -3x = 25 Divide each side by '-3'. x = -8.333333333 Simplifying x = -8.333333333Subproblem 2
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Solution
x = {-8.333333333, 5}
| s=1.5t-2 | | 2x^4+12x^2-7=0 | | 4a=13*25 | | 1,1,3+x=4,3,4 | | 3x+6=19x-15 | | -2(3n+3)=4 | | 9(y-1)-7(2y+1)=10 | | x+4=-5 | | -12=-3/7z | | 12x-6-12=7+12x-12 | | 2x+8+3x+-6=4findx | | A=j+p | | 6a-3=40 | | 9-2(7x-8x)=4x-3 | | C=5/9(95-32) | | 3x-7x+13x= | | -13+3=-39+17x | | -7c+22=6c-4 | | 3X+5FORX=8 | | 4(4x+7y)=69 | | y^3+15y^2+54y=0 | | 12x-6-1=27x+18-10x | | x^2-x^1/2=0 | | 5x=121 | | 6-t=1 | | -7x-6x-3=42 | | x^2=x^1/2 | | 5.6m+1.35=-51.85 | | t/3-7=11 | | .05(x)+.06(y)=612 | | 8x^4+4x^3-14x^2-9x+2=0 | | 5r+6t=3r-2 |